Relasi Kuasa Negara-Agama dan Produksi Otoritas Keagamaan di Turki: Dari Kemalisme hingga AKP - Ardi Kurniawan; Muhammad Darwis Hude; Nur Rofiah; Nurul Qomarudin (CV. Era Digital Nusantara, 2026)
Turkey represents a distinctive model of state-controlled secularism, in which religion is not institutionally separated from the state but is administered through the Diyanet İşleri Başkanlığı (Presidency of Religious Affairs). This study examines how state–religion power relations have shaped religious authority, socio-religious practices, and patterns of resistance from the Kemalist period to the Justice and Development Party (AKP) era. Employing a qualitative library research design, this study analyzes a purposively selected corpus of state policy documents, official Diyanet publications, peer-reviewed journal articles, scholarly books, and historical studies published primarily between 2011 and 2025, supplemented by seminal theoretical works. The data were examined using qualitative content analysis and interpreted through Michel Foucault's concepts of power, governmentality, and pastoral power. The findings indicate that state control over religious institutions encouraged the standardization of Sunni religious authority through Diyanet while limiting the institutional recognition of non-mainstream religious communities, particularly the Alevi community and several Sufi orders. The study further demonstrates that the transition from the secular-Kemalist establishment to the AKP government did not diminish state intervention in religious affairs but rather reoriented Diyanet from safeguarding republican secularism toward expanding Islamic-conservative religious discourse in the public sphere, thereby generating new forms of negotiation and resistance among secular and minority religious groups. This article contributes to the literature by offering a Foucauldian interpretation of Turkish secularism as a dynamic form of state-managed religious governance, highlighting the continuity and transformation of state power across different political regimes rather than a simple transition from secularism to religiosity.